Pengaruh Edukasi Terhadap Mekanisme Koping Pasien Gagal Ginjal Kronik Dengan Pre Hemodialisa di RSUD Dr. M. Haulussy Kota Ambon - Vernando Yanry Lameky; Alisye Siahaya (MOLUCCAS HEALTH JOURNAL, 2021)
Coping mechanism is an active process which uses internal resources and develops new behaviors that aim to grow strength in the individual, reduce the impact of anxiety and even stress in life. The purpose of this study was to determine the effect of education on the coping mechanisms of chronic renal failure patients with pre hemodialysis. This research method is a quasi-experimental design with one group pretest-posttest. The sampling technique used was the accidental sampling method, as many as 60 respondents. The results of the Wilcoxon test showed that the P value = 0.004 = 0.05, which means that there is an effect of education on the coping mechanisms of patients with chronic kidney failure before and after being given education. Suggestions for patients are to continue to increase knowledge and be active in health education activities. Suggestions for health agencies are to provide optimal counseling so that patients are able to use adaptive coping mechanisms.Keywords: Education; Chronic renal failure; Hemodialysis; Coping mechanism